Readiness to Face Digital Audits, Digital Intelligence, and Technology Adaptability: Interest in the Future Auditor Profession - Silfi Yaturrohmah; Novi Darmayanti; Isnaini Anniswati Rosyida (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of digital technologies such as artificial intelligence (AI), big data analytics, and data-based audit systems has significantly transformed auditing practices. These changes require auditors to possess digital readiness, digital intelligence, and the ability to adapt to technological developments. This study aims to analyze the influence of readiness to face digital audits, digital intelligence, and technology adaptability on accounting students’ interest in pursuing the auditor profession in the future. This research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 104 accounting students from several universities in Lamongan Regency using purposive sampling techniques. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results show that readiness to face digital audits has a positive and significant effect on students’ interest in becoming future auditors. Digital intelligence also has a positive and significant influence on the interest in the auditor profession. In addition, technology adaptability significantly and positively affects students’ interest in pursuing auditing careers. Simultaneously, these three variables explain 65.6% of the variance in the interest in the auditor profession. These findings indicate that digital readiness, technological understanding, and the ability to adapt to technological developments in auditing are important factors that encourage accounting students to choose the auditor profession in the era of digital transformation. This study contributes to the development of auditor professional readiness models and supports the strengthening of technology-based auditing curricula in higher education.